Automatism and Mental Disorder in Scots Criminal Law. Issue 2 (May 2015) - Shaw, Elizabeth
<x xml:space="preserve">Abstract</x> In this article, Elizabeth Shaw examines the rule of Scots law that mental abnormality can sometimes entirely eliminate a person's criminal responsibility for her actions. Two separate defences are considered: (1) mental disorder excluding responsibility and (2) automatism. The former is a new statutory defence, replacing the old defence of insanity, which was created following a report by the Scottish Law Commission. That report ignored automatism, an omission argued by the author to be unfortunate since automatism and the mental disorder defence are very closely related. By looking at the mental disorder defence in isolation, the Commission missed an opportunity to make sure that the criminal law takes a philosophically coherent and practically workable approach to people with mental abnormalities. The author's analysis of the Scots law is undertaken in comparison with legal developments in the same field in English law.